Characterization of myosin II regulatory light chain isoforms in HeLa cells. Issue 12 (13th January 2016) - Kondo, Tomo; Okada, Morihiro; Kunihiro, Kayo; Takahashi, Masayuki; Yaoita, Yoshio; Hosoya, Hiroshi; Hamao, Kozue
Abstract : Myosin II regulatory light chain (MRLC) is canonically known as a subunit of conventional myosin (myosin II), which tunes cytoplasmic contractility in cells. Recent studies have also revealed the noncanonical functions of MRLC, such as engagement with other proteins including unconventional myosins. Three MRLC isoforms (MRLC1, MRLC2, and MRLC3) are known in humans. The characteristics of MRLC2 are well known, but those of MRLC1 and MRLC3 are unclear; therefore, the properties of the three MRLC isoforms were investigated. The MRLCs were all phosphorylated at Thr18/Ser19, which is required for myosin II stimulation. MRLC mRNAs were expressed at the same level throughout the cell cycle in HeLa cells. The MRLCs colocalized with each other and their turnover rate was similar to that of myosin II heavy chain. Depletion of all the MRLCs perturbed cell spreading. The overproduction of MRLC2 or MRLC3, but not MRLC1, could effectively compensate for this defect, suggesting that MRLC2 and MRLC3 play dominant roles in cell spreading. Finally, computer simulations of the three‐dimensional protein structures indicated that the location of the N‐terminus of MRLC1 differs from that of MRLC2 or MRLC3, depending on its sequence. Thus, these MRLC isoforms have overlapping but distinct functions have been proposed. © 2015 Wiley Periodicals, Inc.